2015
DOI: 10.3340/jkns.2015.58.3.286
|View full text |Cite
|
Sign up to set email alerts
|

Neurilemmoma of Deep Peroneal Nerve Sensory Branch : Thermographic Findings with Compression Test

Abstract: We report a case of neurilemmoma of deep peroneal nerve sensory branch that triggered sensory change with compression test on lower extremity. After resection of tumor, there are evoked thermal changes on pre- and post-operative infrared (IR) thermographic images. A 52-year-old female presented with low back pain, sciatica, and sensory change on the dorsal side of the right foot and big toe that has lasted for 9 months. She also presented with right tibial mass sized 1.2 cm by 1.4 cm. Ultrasonographic imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Thermography has great potential for improving the diagnosis of neuropathy (6,14). Dysfunction of a nerve or a local musculoskeletal disorder could be linked with varying temperature patterns, such as local hypothermia or hyperthermia of an extremity (14)(15)(16). The measurement of skin temperature with infrared thermography has been claimed as an objective method to appraise the sequel of regional blocks, such as epidural anesthesia, infraclavicular brachial plexus block, and lumbar sympathetic block (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermography has great potential for improving the diagnosis of neuropathy (6,14). Dysfunction of a nerve or a local musculoskeletal disorder could be linked with varying temperature patterns, such as local hypothermia or hyperthermia of an extremity (14)(15)(16). The measurement of skin temperature with infrared thermography has been claimed as an objective method to appraise the sequel of regional blocks, such as epidural anesthesia, infraclavicular brachial plexus block, and lumbar sympathetic block (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…Thermography has great potential for improving the diagnosis of neuropathy ( 6 , 14 ). Dysfunction of a nerve or a local musculoskeletal disorder could be linked with varying temperature patterns, such as local hypothermia or hyperthermia of an extremity ( 14 - 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cho et al, performed statistical analysis and showed that the sensitivity to clinical symptoms was 88.6% and the accuracy of surgical findings was 86.4% in patients with multiple disc lesions, which is of particular clinical value in diagnosing recurrent disc lesions [ 30 ]. Ryu et al, used DITI for neurilemmoma of the deep peroneal nerve for the compression test [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Schwannoma runs a varied symptomatology from asymptomatic phase to mild-to-severe phase of nerve involvement [ 13 ]. In our case, symptoms occurred as a result of nerve compression caused by the growth of the tumorous mass.…”
Section: Discussionmentioning
confidence: 99%
“…Schwannomas are most commonly seen in head and neck (25–45%) [ 17 ], mediastinum (20%) [ 18 ], upper extremity (19%) [ 19 ], retroperitoneum (5–10%) [ 20 ], pelvis (<0.5%) [ 21 ], and lower extremities (13.5–17.5%) [ 22 ]. Various studies in the literature reported that schwannomas are common in the anterior and flexor areas of the upper extremities and the posterior aspects of the lower extremities [ 12 , 13 ]. The review of lower extremity schwannoma from 2013 to 2020 is tabulated in [ Table 1 ] [ 10 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%